Modulation of the NF-κB Pathway by Bordetella pertussis Filamentous Hemagglutinin - Abramson, Tzvia (Public Library of Science, 2008)
BACKGROUND: Filamentous hemagglutinin (FHA) is a cell-associated and secreted adhesin produced by Bordetella pertussis with pro-apoptotic and pro-inflammatory activity in host cells. Given the importance of the NF-κB transcription factor family in these host cell responses, we examined the effect of FHA on NF-κB activation in macrophages and bronchial epithelial cells, both of which are relevant cell types during natural infection. METHODOLOGY/PRINCIPAL FINDINGS: Exposure to FHA of primary human monocytes and transformed U-937 macrophages, but not BEAS-2B epithelial cells, resulted in early activation of the NF-κB pathway, as manifested by the degradation of cytosolic IκBα, by NF-κB DNA binding, and by the subsequent secretion of NF-κB-regulated inflammatory cytokines. However, exposure of macrophages and human monocytes to FHA for two hours or more resulted in the accumulation of cytosolic IκBα, and the failure of TNF-α to activate NF-κB. Proteasome activity was attenuated following exposure of cells to FHA for 2 hours, as was the nuclear translocation of RelA in BEAS-2B cells. CONCLUSIONS: These results reveal a complex temporal dynamic, and suggest that despite short term effects to the contrary, longer exposures of host cells to this secreted adhesin may block NF-κB activation, and perhaps lead to a compromised immune response to this bacterial pathogen.